La escultura de Alberto Giacometti como referente para una propuesta escultórica de los trabajadores ladrilleros del cantón Catamayo - Flores Flores, Mónica Yesenia (2015)
The project places in the analysis of theoretical, technical and aesthetic characteristics of Alberto Giacometti sculpture, taking Ecuador as a managing motive to Catamayo Loja ladrilleros-, valuing his living conditions, by means of the suitable utilization of expressive resources and technical rudimentary procedures, creating an artistic - handcrafted link of the way his productive activities, contributing hereby with sculptural alternatives, based on previous analyses of the reality of the way by means of a qualitative study, in addition the methods analytical and inductive allowed to obtain information, then to proceed with the accomplishment of the works. The offer involves the use of the clay, raw material used for the production of brick and that is obtained in the same place. For the sculptural development, there appears a new emergence of the sculptural expression, taking the figure humanizes " the ladrilleros " as principal modal, determining his activity and the existence itself in the creative process, finally spectator spreads it across a sculptural exhibition as way of entail between artist